Antileishmanial activity and synergistic effects of amphotericin b deoxycholate with allicin and andrographolide against leishmania martiniquensis in vitro - Nuchpicha Intakhan (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Leishmania (Mundinia) martiniquensis is a causative agent of visceral leishmaniasis, but in HIV-infected patients both visceral and disseminated cutaneous leishmaniasis are presented. Recurrence of the disease after treatment has been reported in some cases indicating that improved chemotherapy is required. In this study, the susceptibility of L. martiniquensis to Amphotericin B deoxycholate (AmB), allicin, and andrographolide was evaluated and the synergistic effects of allicin or andrographolide combined with AmB against L. martiniquensis intracellular amastigotes in mouse peritoneal exudate macrophages (PEMs) were investigated in vitro for the first time. The results showed that L. martiniquensis was highly susceptible to AmB as expected, but allicin and andrographolide had selectivity index (SI) values greater than 10, indicating promise in both compounds for treatment of host cells infected with L. martiniquensis. Four AmB/allicin combinations presented combination index (CI) values less than 1 (0.58–0.68) for intracellular amastigotes indicating synergistic effects. The combination with the highest dose reduction index (DRI) allowed an approximately four-fold reduction of AmB use in that combination. No synergistic effects were observed in AmB/andrographolide combinations. The data provided in this study leads for further study to develop novel therapeutic agents and improve the treatment outcome for leishmaniasis caused by this Leishmania species.